Mapping short-range order at the nanoscale in metal-organic framework and inorganic glass composites - Laulainen, Joonatan E. M.; Johnstone, Duncan N.; Bogachev, Ivan; Longley, Louis; Calahoo, Courtney; Wondraczek, Lothar; Keen, David A.; Bennett, Thomas D.; Collins, Sean M.; Midgley, Paul A. (Nanoscale, 2022)
Characterization of nanoscale changes in the atomic structure of amorphous materials is a profound challenge. Established X-ray and neutron total scattering methods typically provide sufficient signal quality only over macroscopic volumes. Pair distribution function analysis using electron scattering (ePDF) in the scanning transmission electron microscope (STEM) has emerged as a method of probing nanovolumes of these materials, but inorganic glasses as well as metal-organic frameworks (MOFs) and many other materials containing organic components are characteristically prone to irreversible changes after limited electron beam exposures. This beam sensitivity requires ‘low-dose’ data acquisition to probe inorganic glasses, amorphous and glassy MOFs, and MOF composites. Here, we use STEM-ePDF applied at low electron fluences (10 e− Å−2) combined with unsupervised machine learning methods to map changes in the short-range order with ca. 5 nm spatial resolution in a composite material consisting of a zeolitic imidazolate framework glass agZIF-62 and a 0.67([Na2O]0.9[P2O5])-0.33([AlO3/2][AlF3]1.5) inorganic glass. STEM-ePDF enables separation of MOF and inorganic glass domains from atomic structure differences alone, showing abrupt changes in atomic structure at interfaces with interatomic correlation distances seen in X-ray PDF preserved at the nanoscale. These findings underline that the average bulk amorphous structure is retained at the nanoscale in the growing family of MOF glasses and composites, a previously untested assumption in PDF analyses crucial for future non-crystalline nanostructure engineering.
CRIS-Team Scopus Importer:2023-04-20